Chatbots: A New Digital Teaching Tool Paradigm in Artificial Intelligence (AI) Technology Among Secondary School Teachers - Mohamed, Asmawati; Ghazali, Norliza; Mohamed Mokhtar, Marzni (Journal of Public Administration and Governance, 2023)
Teachers around the world are committed to improving student-centered learning, intending to enhance the digital teaching tool in the classroom, in tandem with the rapid evolution of technology. In addition, as a teacher, education is one of the sectors that play an essential role in preparing students for the changes, as students begin to recognize what they are learning on the first day of formal education. Consequently, exploring teachers’ experience and reviewing the challenges in teaching, is in line with the current digital era. The implementation has significance important in the scenario of Industrial Revolution 4.0 (IR4.0). One of the pillars, Artificial Intelligence (AI) Technology, which is defined as the ability of a computer or a computer-controlled robot to perform tasks that are normally performed by humans has given a dynamic viewpoint in various fields, especially in teaching. Nowadays, decision-making is simplified by artificial decision-making, which does not require the presence of a human. As a result, Chatbots as in AI Technology provide a new paradigm for teachers at school, and the mushrooming of digital mediums in education enhances the capability of teaching by using chatbot applications in the lessons. The purpose of this study is to explore Chat Bots in AI Technology as a digital teaching tool among Secondary School Teachers. The researcher used a qualitative case study guide with the purposive sampling method with three research questions to gather data through semi-structured interview questions and document review. Next, the researcher used manual coding to create themes for the findings. All in all, the informants are sharing the concept, the use, and the challenges based on content representation, the students’ interactions in previous experiences, assessments, and feedback. How teachers respond in depth led to the researcher discovering the need for training, professional development, and future classrooms for secondary education.